2012
DOI: 10.1007/s12104-012-9439-1
|View full text |Cite
|
Sign up to set email alerts
|

1H, 13C and 15N resonance assignments of the N-terminal domain of Vta1–Vps60 peptide complex

Abstract: Vta1 and Vps60 are two ESCRT associated proteins, their direct interaction enhances Vps4 ATPase activity. The N-terminal domain of Vta1 (residues 1–167aa, named as Vta1NTD) contains two tandem MIT domains, which specifically recognize Vps60 and Did2 but not other ESCRT-III subunits. The fragment Vps60 (128–186aa) was reported to display full activity of Vps60, which stimulates Vps4 ATPase in a Vta1-dependent manner. To study the structural basis for the interaction between Vta1 and Vps60, as a first step, here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…2E)3334. The helix α4 is much longer in Vta1NTD-Did2 176–204 than that in free Vta1NTD crystal structure, but similar to the observation in NMR structure of Vta1NTD bound to Vps60 128–186 333435. This observation is consistent with our previous secondary structure prediction of free Vta1NTD using the programs CSI38 and TALOS3940 based on the assignments of NMR signals belonging to the backbone atoms of Vta1NTD.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…2E)3334. The helix α4 is much longer in Vta1NTD-Did2 176–204 than that in free Vta1NTD crystal structure, but similar to the observation in NMR structure of Vta1NTD bound to Vps60 128–186 333435. This observation is consistent with our previous secondary structure prediction of free Vta1NTD using the programs CSI38 and TALOS3940 based on the assignments of NMR signals belonging to the backbone atoms of Vta1NTD.…”
Section: Resultssupporting
confidence: 90%
“…The complex Vta1NTD- Did2 176–204 structure shows that the bound Vta1NTD still has two MIT domains, each of them is composed of three α-helices (MIT1: helices α1, α2 and α3; MIT2: helices α5, α6 and α7; respectively), almost similar to those observed in its free state and in its complex with Vps60 128–186 2933343536. The backbone atoms belonging to MIT1 and MIT2 regions of bound Vta1NTD have RMSD values of 1.7 Å and 1.8 Å with those of free Vta1NTD (Fig.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…The ESCRT-III subunits Did2 and Vps60 bind to the Vta1 amino-terminal MIT domains (37). Recent structural analysis of these associations revealed that ESCRT-III binding does not effect significant conformational changes within the MIT domains (46,47,55). Removal of the Vta1 MIT domains similarly did not enhance Vta1 stimulation of Vps4 (43).…”
Section: Discussionmentioning
confidence: 99%